Job Stress and Burnout Among Employees Working in Terrorist-Ridden Areas - Soomro, Shuaib Ahmed; Gadehi, Akhtiar Ali; Xu, Xu Hongyi; Shaikh, Sarfaraz Ahmed (Frontiers in Psychology, 2021)
The article examines the relationships of effort-reward imbalance (ERI) on employee stress, three facets of job burnout (BO), organizational (in)justice (OJ) and sensitivity to terrorism (STT). This study uses the effort-reward imbalance (ERI) framework as a job stress model. After describing terrorism and a brief discussion on organizational justice and some of the challenges associated with it, we introduced 'sensitivity to terrorism' as a moderator in the ERI framework. Using a 432 sample size of questionnaire data collected from two big cities where terrorist attacks are rampant and received during a period when terrorist attacks were at a peak. After analyzing data in EFA, results from the hierarchical regression analysis provided support for our developed model. Overall, the statistical model is significant (p<.05). We found significant relationships between ERI and facets of BO. Organizational (in)justice mediated the influence of ERI on facets of BO. We also found that STT significantly moderated ERI and facets of burnout. The article concludes with some implications and guidelines for future research.